Personality and mood of former elite male athletes - a descriptive study - Bäckmand, H.; Kaprio, J.; Kujala, U.; Sarna, S. (International Journal of Sports Medicine, 2001)
The purpose of this study was to describe the personality and mood of former athletes in middle and old age. The subjects were male athletes who represented Finland from 1920 to 1965 and male referents who were classified as healthy at 20 years of age. The athletes were classified into a total of five athlete groups (endurance, power/combat, power/individual, team, shooting) and one reference group. Four personality scales (extroversion, neuroticism, life satisfaction, and hostility) were used in a baseline questionnaire in 1985 (athletes N = 1040, referents N = 777). Anxiety and depression were assessed in a follow-up in 1995 (athletes N = 758, referents N = 578) with a shortened version of the BSI-53 symptom inventory. According to ANCOVA there were group differences in extroversion, neuroticism, and life satisfaction but not in hostility. Athletes who had participated in power/combat sports and team sports were more extroverted than referents. Endurance sport and shooting sport athletes had lower neuroticism scores than the referents. Endurance, power/combat, team and shooting sport athletes were more satisfied with their lives than were the referents. Discriminant analysis mainly supported these findings. Differences regarding depression were also statistically significant between the groups as referents were more depressed than endurance sport and team sport athletes. No group differences in anxiety were found. The subjects described in this study are unique in number of respects. Bearing in mind the limitations of the study subjects, it is concluded that former athletes differ from nonathletes in some personality characteristics and depression.